IL‐17A aggravates asthma‐induced intestinal immune injury by promoting neutrophil trafficking. Issue 3 (11th July 2022) - Hong, Yanfei; Chu, Zhulang; Kong, Jingwei; Li, Qiuyi; Li, Na; Liu, Liting; Wu, Tong; Liu, Jiajing; Ge, Dongyu; Li, Jie; Peng, Guiying
Abstract: With the concept of the gut–lung axis reinforced in recent years, emerging evidence has shown that intestinal homeostasis is vital for lung health. Nevertheless, the impacts of lung homeostasis on intestinal tracts and their mechanism are rarely studied. Our results showed that papain‐induced asthmatic mice exhibited apparent colonic injuries compared with controls, including increased intestinal permeability, neutrophil and Th17 infiltration in the colonic lamina propria. Moreover, the intranasal administration of papain aggravated such colonic injuries in mice with dextran sulfate sodium‐induced colitis, as evidenced by increased occult blood scores, shortened colon length, and accumulated neutrophils. The level of IL‐17A was also higher in the serum of asthmatic mice than wild‐type mice. Interestingly, the pathologic scores, the proportion of Th17 cells, and neutrophil infiltration in the colon were markedly reduced after IL‐17A blocking. Similarly, longer length, lower pathologic scores, and fewer neutrophils were also observed in the colon of IL‐17‐deficient asthmatic mice. More importantly, we demonstrated that severe gastrointestinal symptoms could accompany clinical asthmatics. The frequencies of Th17 cells and the mRNA expression of IL‐17A in the peripheral blood of these patients were significantly enhanced. Besides, the gastrointestinal symptom rating scale scores positively correlated with the frequencies of Th17 in asthmatics. These findings enlighten that IL‐17A aggravates asthma‐induced intestinal immune injury by promoting neutrophil trafficking, which facilitates the exploration of new potential biomarkers to treat asthma. Graphical Abstract: IL‐17A aggravates asthma‐induced intestinal immune injury by promoting neutrophil trafficking, which facilitates the explorations for new potential biomarkers for the treatment of asthma.